Mekanisme Pasar Dan Regulasi Harga Perspektif Ibn Taimiyah Dan Ibn Khaldun: Sebuah Kajian Komparatif - Nur Muthmainnah (JES (Jurnal Ekonomi Syariah), 2019)
The role of Islamic economics in regulating the mechanism of market activity at this time is a very important factor, for the advancement and development of world economy in general and especially for the nation of Indonesia, this now the rate of the  economy is still quite slow, after the monetary crisis in this country. As well as the regulation (determination) in the Islamic economic concept of determining is done by market forces namely the power of demand and offer. The research is the result of qualitative research that aimed answering the question of how Ibn Taimiyah thought about market mechanism and price regulation, how Ibn Khaldun thought about market mechanism and price regulation, and how the comparative analysis of Ibn Taimiyah and Ibn Khaldun's thought about market mechanism and price regulation. The research approach used a comparative descriptive or comparison approach, the data collection is done by reviewing the books.of  figures Islamic economic thinkers. The results of the research of Ibn Taimiyah and Ibn Khaldun's thought about market mechanisms and price regulation, Ibn Taimiyah and Ibn Khaldun opinion that the ups and downs of prices in the market are determined by the level of demand and offer  by a goods and prohibit the interference of any party in determining the price during the market is normal, and in the minds of the two figures there are some differences and equation in explaining about market mechanism and price regulation. Keywords: Ibn Taimiyah, Ibn Khaldun, Market Mechanism and Price Regulation